Quantifying yield and water productivity gaps in an irrigation district under rotational delivery schedule - Angella, Gabriel Augusto; García Vila, Margarita; Lopez, Juana Maria; Barraza, Gabriela Alejandra; Salgado, Ramiro; Prieto Angueira, Salvador; Tomsic, Pablo Daniel; Fereres Castiel, Elías (2018)
Removal of irrigation network limitations under a rotational delivery schedule has been focused on improving infrastructures without paying sufficient attention to improving management. We developed a methodology to assess the yield and water productivity gaps in the Río Dulce irrigation system, Santiago del Estero, Argentina. The AquaCrop model was used to determine the potential and attainable yields of maize and cotton under different water management scenarios. Actual yields and irrigation practices were determined by field surveys and farmers interviews. The AquaGIS tool facilitated the assessment of the spatial and temporal variations in yield using a daily climatic database of 26 years. The average yield gap (potential minus actual) amounted to 6 t ha−1 in maize and 2 t ha−1 in cotton. The average water productivity gap was 7 kg ha−1 mm−1 in maize and 2 kg ha−1 mm−1 in cotton. By a more effective use of the rotational delivery schedule, the yield gap could be partially closed, in particular if associated with other agronomic practices, namely nitrogen fertilization. The approach demonstrated the potential of combining field data collection with the use of AquaCrop to quantify the yield and WP gaps, and to propose management recommendations for closing the gaps.